Análisis estratégico hacia el posicionamiento en el mercado de productos saludables proteicos en Lima Metropolitana. Caso Moringa - Sanchez Isuiza, Fernando Thomas (2021)
This study analyzes the factors that influence the market for healthy products in Metropolitan Lima, proposing alternatives to achieve a strategic position through Porter's forces applied to the moringa, which is a tree from Asia with multiple nutritional, therapeutic and antioxidant properties. In this sense, moringa derivatives such as leaf powder and seed oil meet many needs, generating long-term benefits such as strengthening the immune system, disease prevention or muscle development. The population used is people over 18 years of age from socioeconomic levels A and B from zones 6 and 7 of Lima, obtaining a sample of 365 people, of which 94% of those surveyed consume healthy protein products and 74% of these have a healthy lifestyle with a preference for supplements and shakes being 49% of the survey. Besides, 68% consider the consumption of these products very important for health and 59% are considerably concerned that they are of natural origin, the frequency of consumption of moringa resulted in that 25% would consume it every day and 32% 2 to 3 times a week being a healthy alternative in the daily diet. There is a location preference in supermarkets in 50%, then in specialized stores in 19% where young people between 18 and 25 years old have a greater presence. Also, the main aspect of the product is the nutritional information and the flavor being 49% and 36% respectively. Therefore, it can be concluded that moringa has potential acceptance in the local healthy market by complementing the diet and being an input for more elaborated products in the food or cosmetic industries.